Penerapan Metode Analytical Hierarchy Process Penentuan Siswa Terbaik Program Tahfidz Qur'an - elvina yunita; Rizaldi Rizaldi; Maulana Dwi Sena (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Yayasan Mutiara Hikmah is an Al-Qur'an-based school, has a mandatory program, namely Tahfidz Qur'an which is taught consistently every day to students. However, madrasas have never done a global ranking on the tahfidz program. The ranking is still limited to each class, there has never been a search for the best candidate in the tahfidz qur'an program. The calculation of the value obtained by students in tahfidz learning is also still manually so that it is prone to errors during calculations and inaccurate results obtained, the calculation process is inefficient because it can take a long time due to manual calculations using bookkeeping and Ms. Excel. Therefore, the researcher proposes a decision support system to assist schools in ranking globally and overcoming all the problems that exist in determining the best students for the tahfidz qur'an program. The decision support system that will be proposed by the researcher is made using Visual Studio 2010. With a calculation process that applies the Analytical Hierarchy Process (AHP) method. The selection of the Analytical Hierarchy Process (AHP) method is because it is good in preparing various priorities that will be selected for ranking.